Influence of feeding weanmor+® to sows on stillborn rate and preweaning mortality - Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
A total of 239 sows (PIC C-22) were used in this experiment. Sows were randomly allotted to one of the two experimental treatments approximately 5 days before their expected farrowing date. Control sows did not receive any topdress; sows on the WEANMOR+® treatment received a single daily topdress of 25 g of WEANMOR+®. Topdressing the sow feed with WEANMOR+® reduced (P<0.06) urine pH, but number of total pigs born, mummied, fostered, died, or weaned were not influenced by treatment (P>0.67). There was a parity group-by-stillborn interaction (P<0.10) in which feeding WEANMOR+® reduced the number of stillborn pigs in the parity 2 to 5 sows, with a numeric increase in stillborns when WEANMOR+® was fed to sows that were parity 6 and over.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Sows; Litter size; Diet acidification; Swine